Immunogenicity of PvVir14-derived peptides to improve the serological diagnosis of Plasmodium vivax infection - Ramayana Morais de Medeiros Brito; Ramayana Morais de Medeiros Brito; Raianna F. Fantin; Raianna F. Fantin; Ana Laura Grossi de Oliveira; Ana Rafaela Antunes Porto; Ana Rafaela Antunes Porto; Isabela de Brito Duval; Isabela de Brito Duval; José Bryan da Rocha Rihs; José Bryan da Rocha Rihs; Lilian Maria Lapa Montenegro Pimentel; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionMalaria, caused by Plasmodium vivax, remains a major global health problem, particularly in tropical and subtropical regions. This study aimed to investigate the potential of PvVir14-derived peptides to improve diagnostic accuracy for P. vivax infections.MethodsThe reactivity of specific PvVir14-derived peptides against sera from acutely infected individuals from endemic and non-endemic areas experiencing a P. vivax malaria outbreak was assessed, as well as their sensitivity, specificity, and immunodominance.ResultsAmong the eight tested peptides (H08, K09, I03, G08, F08, H04, L06, and N04), H08, G08, and L06 showed significantly higher IgG reactivity in sera from individuals living in endemic areas, mainly within those with multiple malaria episodes. After a P. vivax outbreak in a non-endemic area, H08 and G08 had the highest IgM frequencies, however, sensitivity and specificity analyses indicated that L06 was the most effective peptide for identifying infected individuals. Depletion ELISA confirmed the immunodominance of L06, G08, and H08 and showed a significant reduction in IgG reactivity to PvVir14. The peptides L06, G08, and H08, showed high sensitivity and specificity as diagnostic tools for P. vivax malaria.ConclusionsThese peptides can improve diagnostic accuracy, especially in endemic areas, providing better support to malaria control and management programs.